2015
DOI: 10.3109/09513590.2015.1103220
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein P is not elevated in gestational diabetes mellitus

Abstract: Selenoprotein P concentrations have been found to be associated with insulin resistance and elevated in patients with type 2 diabetes mellitus (DM). The aim of the present study was to investigate circulating selenoprotein P level and its possible relationship with metabolic parameters in gestational diabetes mellitus (GDM). Plasma selenoprotein P concentrations were measured in 30 pregnant women with GDM, 35 pregnant women without GDM and 22 healthy nonpregnant women. No difference in selenoprotein P levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Similarly, di Giuseppe et al, based on MRI imaging, noted inverse relations of serum selenoprotein P concentrations with several metabolic indices [ 42 ]. Furthermore, Altinova et al did not show any difference in SeP level in diabetic versus non-diabetic pregnant women [ 23 ]. Finally, Polyzos et al in a recently published study revealed decreased SeP levels in patients with definite NASH (nonalcoholic steatohepatitis) compared with controls, and they did not rely on the severity of steatosis, fibrosis or lobular and portal inflammation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, di Giuseppe et al, based on MRI imaging, noted inverse relations of serum selenoprotein P concentrations with several metabolic indices [ 42 ]. Furthermore, Altinova et al did not show any difference in SeP level in diabetic versus non-diabetic pregnant women [ 23 ]. Finally, Polyzos et al in a recently published study revealed decreased SeP levels in patients with definite NASH (nonalcoholic steatohepatitis) compared with controls, and they did not rely on the severity of steatosis, fibrosis or lobular and portal inflammation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased hepatic SeP has been related to reduced glucose tolerance as well as higher fasting glucose levels [ 3 , 21 ]. On the other hand, as some researchers suggested that increased SeP concentrations may be a secondary condition to DM or reported contradictory outcomes, it seems highly possible that SeP is involved in glucose homeostasis and metabolic disorders, although not many definite conclusions can be drawn [ 12 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…An early paper showed that SELENOP concentrations were unchanged in pregnant women with gestational diabetes compared with those without gestational diabetes 10 . In that paper, the average HbA1c in pregnant women with gestational diabetes was 5.4%.…”
Section: Discussionmentioning
confidence: 99%
“…First, SELENOP concentrations were reported to be elevated in people with type 2 diabetes, prediabetes, and non-alcoholic fatty liver disease 1 , 8 , 9 . However, pregnant women with gestational diabetes showed unchanged plasma levels of SELENOP compared with those without gestational diabetes 10 . In young children, increased SELENOP concentrations were reported to be negatively associated with certain components of metabolic syndrome, such as waist circumference and blood pressure 11 .…”
Section: Introductionmentioning
confidence: 87%
“…However, quantification of SELENOP is challenging, and reported serum concentrations of SELENOP differ considerably between assays and research laboratories. Recently, the following concentrations of SELENOP in serum or plasma of healthy subjects have been reported: 6.7 (5.3–9.1) µg/L in a Turkish [14], 362.0 (252.5–694.5) µg/L in a South Korean [15], 5.3±1.1 mg/L in a Japanese [16], and 52.3±39.1 mg/L in a Chinese/Australian study [17]. These concentration ranges differ by almost 4 orders of magnitude, highlighting that there is an urgent need for a better characterization and calibration of SELENOP assays used in clinical analyses, and a need for a uniformly accepted reference material.…”
Section: Introductionmentioning
confidence: 97%